MEMBANGUN PERATURAN DAERAH BIDANG PERTAMBANGAN MINERAL DAN BATUBARA BERBASIS CITA HUKUM PANCASILA - Andi Sugirman (Masalah-Masalah Hukum, 2014)
Building the legal product of a regional regulation on mineral and coal mining is the authority of regional governments. In implementing their authority, they are required to apply Pancasila and embrace the 1945 Constitution of the Republic of Indonesia. Pancasila consisting of five precepts is a legal ideal that should be incarnated in the legal product of a regional regulation on mineral and coal mining. The incarnation of the legal ideal of Pancasila through the legal product of a regional regulation on mineral and coal mining will have the implication on mineral and coal mining management based on the legal ideal of Pancasila. Therefore, building the regional regulation on mineral and coal mining must be based on the normative-juridical aspect as the basis for the making of laws and the theoretical aspect based on the legal ideal of Pancasila. Keywords: The Legal Ideal of Pancasila, Mining, Regional Regulation Membangun produk hukum perturan daerah pertambangan mineral dan batubara merupakan kewenangan penyelenggara pemerintahan daerah, dalam menjalankan kewenangannya   berkewajiban mengamalkan Pancasila dan memegang teguh UUD NRI Tahun1945. Pancasila yang terdiri dari kelima sila adalah merupakan cita hukum  seharusnya dijabarkan dalam produk hukum perturan daerah pertambangan mineral dan batubara. Penjabaran cita hukum Pancasila melalui produk hukum pertambangan mineral dan batubara akan berimplikasi terhadap pengelolaan pertambangan mineral dan batubara berbasis cita hukum Pancasila, karena itu membangun peraturan daerah pertambangan mineral dan batubara harus didasarkan pada aspek yuridis normatif sebagai landasan pembuatan peraturan perundang-undangan, serta aspek teoritik berbasis cita hukum Pancasila. Kata Kunci : Cita Hukum Pancasila, Pertambangan, Peraturan Daerah